2018
DOI: 10.1172/jci.insight.98306
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 signaling mediates intrauterine inflammation and chorio-decidua neutrophil recruitment and activation

Abstract: Neutrophil infiltration of the chorioamnion-decidua tissue at the maternal-fetal interface (chorioamnionitis) is a leading cause of prematurity, fetal inflammation, and perinatal mortality. We induced chorioamnionitis in preterm rhesus macaques by intraamniotic injection of LPS. Here, we show that, during chorioamnionitis, the amnion upregulated phospho-IRAK1-expressed neutrophil chemoattractants CXCL8 and CSF3 in an IL-1-dependent manner. IL-1R blockade decreased chorio-decidua neutrophil accumulation, neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
131
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(146 citation statements)
references
References 93 publications
(105 reference statements)
13
131
2
Order By: Relevance
“…Data in the non-human primate demonstrate that infectious agents confined to the choriodecidua induce preterm labor at a much lower frequency compared to infection in the amniotic fluid (81)(82)(83). Our data demonstrate that macromolecules such as cytokines (IL1ra) do not efficiently cross the amniotic epithelial barrier but readily cross the placenta from the mother to the fetus (84). Thus, the evaluation of compartment-specific mechanisms of inflammation is important.…”
Section: Vaginal Microbiomementioning
confidence: 81%
See 2 more Smart Citations
“…Data in the non-human primate demonstrate that infectious agents confined to the choriodecidua induce preterm labor at a much lower frequency compared to infection in the amniotic fluid (81)(82)(83). Our data demonstrate that macromolecules such as cytokines (IL1ra) do not efficiently cross the amniotic epithelial barrier but readily cross the placenta from the mother to the fetus (84). Thus, the evaluation of compartment-specific mechanisms of inflammation is important.…”
Section: Vaginal Microbiomementioning
confidence: 81%
“…Neutrophils infiltrating the choriodecidua are largely of maternal origin (147,148), while neutrophils in the amniotic fluid are largely of fetal origin (149), although a recent study reported mixed fetal/maternal origin of neutrophils in the amniotic fluid (150). During normal pregnancy, there are small numbers of neutrophils, but the numbers increase dramatically during IUI presumably due to secretion of neutrophilic chemotactic factors such as IL-8 by the amnion (84,108). CD15 + neutrophils represent the most abundant leukocyte population in AF from women with intraamniotic infection/inflammation (151).…”
Section: Neutrophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…All these genes may be in one way or another related to PTB: CCRL2 and CXCL2 belong to inflammatory pathways [55,56], GPR84 is a receptor of fatty acids also related to inflammation [57]. BCL2A1 and CHI3L1 were recently associated with chorioamnionitis in monkey and human [58], SLC16A10 is up-regulated in the mid-gestational placenta [59] and SAMSN1 is a poorly characterized gene that may be involved in differentiation of lymphocytes B [60]. The fact that these subsets of genes overlap in both studies using different experimental techniques stresses that they should be a target of further research of PTB.…”
Section: Discussionmentioning
confidence: 99%
“…Resident immune cells were followed by live imaging. Notably, neutrophils are normally scarce in the maternal-fetal membranes in the absence of infection (47). Phagocytic cells were present at the surface as soon as 15 min pi.…”
Section: Discussionmentioning
confidence: 99%